A new method for handoff target network selection - Jyoti Madaan; Sunanda Gupta; Pratima Manihas (Institute of Advanced Engineering and Science, 2019)
In wireless communications of fourth generation the expectation to assimilate a hypothetically numerous heterogeneous wireless technologies are happened under consideration of a novel step toward worldwide smooth access. The advancement in wireless networks increases the challenges of mobility management as well the challenges of merging a various number of wireless networks. Out of those the main challenge for smooth movement is the accessibility of consistent vertical (intersystem) and horizontal (intra-system) handoff processes. So to improve the quality of service and to provide always best connected services all the time, the handoff decision algorithm must select an optimum target network from the available candidate networks. The purpose of this paper is to provide a mechanism for selecting an optimum target network from the available networks. This method is devised for maximizing the user satisfaction level, by selecting the “best” network as the handover target network among multiple candidate networks.